Vegetable fibre reinforced concrete composites: a review - Pacheco-Torgal, F. (2009)
The current manuscript deals with the subject of natural fiber reinforced concrete. It includes fiber characteristics, properties and the description of the treatments that improve their performance; it covers the compatibility between the fibers and the cement matrix and also how their presence influences cement properties like setting time or the interfacial transition zone. It also includes the properties and durability performance of concrete reinforced with natural fibers. Future research trends are also presented.